Desenvolvimento e otimização de métodos analíticos para sulfato de salbutamol inalatório pressurizado dosimetrado - Ana Carolina Guimaraes Ribeiro (2015)
Bronchodilator drugs administered by inhalation are used in the treatment of respiratory diseases because they act directly on the therapeutic target and cause fewer systemic adverse effects. Among them is salbutamol sulphate (SS) for inhalation which is widely administered and listed in the National List of Essential Drugs/RENAME. The physical-chemical quality control tests for these products are little known among Brazilian laboratories and there are no instructions for such testing in the Brazilian Pharmacopeia. Thus, the objective of this work was to develop analytical methods for evaluating the physicochemical quality of inhalation medications, using SS pressurized metered-dose inhaled/pMDI, based on the instructions of the United States and British pharmacopeias. The developed quantitation of SS by HPLC using Doehlert matrix followed the conditions: C18, 100x4.6 mm, 3.5 µm 25 °C, mobile phase 0.1% ammonium acetate (w/v):methanol (78:22), flow rate 0.6 mL/min, 225 nm, in the linear concentration range from 1.5 to 12.0 µg/mL (R2 0.9999). For the related substances test the total content was below the limit of 0.5%. The identification by infrared spectrophotometry and HPLC (3.48 min, k 1.85) was positive against SS standard. The assay and the uniformity of released dose (URD) were developed through the emitted dose pickup device (dosage unit sampling apparatus/DUSA). The SS content found was 111.69% of the labeled value (LV) and the doses taken in URD test were within the range 75.0 to 125.0% LV. For the aerodynamic particle size distribution test (APD), two methods have been developed through the Andersen Impactor Cascade (ACI) and Glass Twin Impinger (GTI). The average particle diameter determined by laser diffraction was 3.48 µm. The results of the validation parameters were in accordance with the specifications of the National Health Surveillance Agency - Ministry of Health/ANVISA-MS. The developed and validated tests for the quality control of inhaled medications are proposed to compose the Brazilian Pharmacopoeia, in order to increase accessibility to specific instructions for Brazilian laboratories.